SM Specialist "Burger ATM" / Nurul Shahira Mohammad - Mohammad, Nurul Shahira (2020)
Our company provides the community with a custom made burger vending machine called Burger ATM especially for those who love custom made burgers and also who do not have time to go for a meal. Burger ATM provided customers with a variety of choices of toppings for the burger to satisfy everyone’s taste and preferences. It also comes with a touchscreen menu where customers can easily choose from and also has a card slot and e-wallets to help customers pay digitally. Hence, they do not have to insert cash into the vending machine anymore.